Personal Hygiene Habits dan Kejadian Flour Albus Patologis pada Santriwati PP AL-Munawwir, Yogyakarta - Umi Sa'adatun Nikmah; Hesty Widyasih (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
Fluor albus is fluid secretion from the woman’s genitals (vagina) and divided into physiological and pathological.Fluor albus is not a disease but most indication of gynecological problems. The most common cause ofpathological fluor albus is infection. Personal hygiene habits are an important factor to avoid an infection whichcauses fluor albus. This study aims to know the correlation between personal hygiene habits with occurrence ofpathological fluor albus, that used cross sectional method with santri as research population in Pondok PesantrenAl-Munawwir Komplek Q. The sampling used purposive and random sampling, with sampling size 106 santri, andused personal hygiene habits and fluor albus questionnaires to collect data. Data analysis used chi-square testand Coefficient Contingency test. Results of the study showed that 52 % santri had bad personal hygiene habitsand 75,5% santri were indicated pathological fluor albus. Statistical tests showed p=0.000 and C=0,517 whichmeans there were positive and significant correlation between personal hygiene habits with occurrence of pathologicalfluor albus. This is indicating when someone has bad personal hygiene habits, so they are experiencingpathological fluor albus.